Schiff Base Derivative of Cyclooctatetraenyl Lanthanoid/NaH Catalytic Systems for the Isomerization of 1,5-Hexadiene - Yousaf, Muhammad; Ghulam Ali, Kulsoom; Parveen, Bushra; Jabbar, Abdul; Badaruddin Ahmad, Hafiz; Ma, Hiyan (Asian Journal of Chemistry, 2010)
The different types of the tridentate Schiff base N-(2-methoxyphenyl)-salicylideneamine derivative of lanthnoid cyclooctatetraenyl complexes [COTLn Schiff base·2THF (Ln = Sm, Eu, Gd and Er)] along with NaH are proved to be a versatile tool for the isomerization of 1,5- hexadiene. The isomerization resulted a mixture of products such as 1,4-hexadiene, 1,3-hexadiene, 2,4-hexadiene, methylenecyclopentane and methyl-cyclopentene. Among these 1,4-hexadiene and methylenecyclopentane were the end products while 1,3-hexadiene, 2,4-hexadiene and methyl-cyclopetene were the intermediates. From the results it is assumed that radius of the metal is an important factor in determining the catalytic efficiency of the complexes.